Cenozoic detachment folding in the southern Tianshan foreland, NW China: Shortening distances and rates. (March 2016) - Tian, Zhonghua; Sun, Jimin; Windley, Brian F.; Zhang, Zhiliang; Gong, Zhijun; Lin, Xu; Xiao, Wenjiao
Abstract: Intracontinental foreland basins with fold-and-thrust belts on the southern periphery of the Tianshan orogenic belt in China resulted from still-active contractional deformation ultimately cased by the India–Asia collision. To quantify the amounts of shortening distance and the rates of deformation, and to decipher the architectural framework, we mapped the stratigraphy and structure of four anticlines in the Kuqa and Baicheng foreland thrust belts in the central southern Tianshan. In the Baicheng foreland thrust belts, Lower Cretaceous Baxigai and Bashijiqike Formations located in the core of the Kumugeliemu anticline are overlain by the Paleocene to Eocene Kumugeliemu Formation, above which are conformable Oligocene through Pleistocene sediments. A disharmonic transition from parallel to unconformable bedding at the boundary of the Miocene Kangcun and Pliocene Kuqa Formations suggests a change from pre-detachment folded strata to beds deposited on top of a growing anticline. Most of the anticlines have steep limbs (70–90°) and are box to isoclinal folds, suggestive of detachment folding or faulted detachment folding (faults that transect a fold core or limb). Shortening estimates calculated from the cross-sections by the Excess area method indicate that the total shortening for the Kelasu, Kuchetawu, Kezile and Yaken sections are 6.3 km, 6.4 km, 5.8 km and 0.6 km, respectively, and the respective depths of the detachment zones are (2.3 km and 6.9 km), 2.3 km, 2.5 km and 3.4 km. Time estimates derived from a paleomagnetic study indicate that the transition to syn-folding strata occurred at ∼6.5 Ma at the Kuchetawu section along the Kuqa river. In addition, according to our field observations and previous sedimentary rate studies, the initial time of folding of the Yaken anticline was at 0.15–0.21 Ma. Therefore, the average shortening rate that began at ∼6 Ma was ∼2 mm/a for the Kelasu, Kuchetawu and Kezile sections. At 0.15–0.21 Ma, the average shortening rate increased to 3–4 mm/a in the Yaken section. Combined with the recent GPS data, the shortening rate in the central southern Tianshan area increased to 4.7 ± 1.5 mm/a at present. We suggest that there was a linear increase in shortening rate in the southern Tianshan foreland basin, which also indicates that the far field stress increased considerably from the late Miocene to Present in response to the India–Asia collision. Graphical abstract: Highlights: The anticlines (e.g. Qiulitag) in this study are a series of detachment folds. Shortening distances (∼12 km) were calculated for the whole cross-section. Initial folding age: Qiulitag and Kumugeliemu (∼6 Ma) and Yaken (0.15–0.21 Ma). Shortening rate increased from ∼2 mm/a (∼6 Ma), to 3–4 mm/a (∼0.2 Ma), to ∼5 mm/a (present). Intracontinental deformation increased from ca.∼6 Ma to present.